Design and SWOT Analysis of Compost Shredder Machine at Waste Processing Sites - Reduce, Reuse, Recycle (TPS-3R) - I Wayan Koko Suryawan (Jurnal Proyek Teknik Sipil, 2022)
Reduce, Reuse, Recycle Waste Management Site, abbreviated as TPS-3R according to Government Regulation No. 27 of 2020, is a place where collection, sorting, reuse, and recycling activities are carried out on a regional scale. This TPS-3R design has a size of 20 x 10 meters. Following the regulations stipulated that the TPS-3R must have an area of more than 200 m2. TPS-3R has separate rooms to process the waste that enters the TPS. Seen here is a room that contains a milling machine or chopping machine and organic waste sifter machine. The innovation provided by TPS-3R is the presence of an organic waste shredder and a compost shredder machine. Both of these machines function to speed up composting and can produce large amounts of compost in a short time. The waste shredder is the most appropriate technology for processing organic waste using a diesel engine with a capacity of 500-700 kg/hour. With the compost shredder machine in TPS-3R, it is hoped to speed up the processing time for sifting the compost material. Accurate cost planning calculates the volume of work, the prices of various materials, and work on a building or project based on actual data.